Vasoactive agents for the management of acute variceal bleeding: A systematic review and meta-analysis - Huaringa-Marcelo, Jorge (2021)
Background & Aims: Vasoactive agents with endoscopic therapy are used to treat acute variceal bleeding (AVB). There are two main groups of vasoactive agents: terlipressin and vasopressin (T-V), and octreotide and somatostatin (O-S). However, the benefit/harm balance is unclear. Our aim was to assess the efficacy and safety of T-V versus O-S for the management of AVB. Methods: We performed a systematic search for randomized controlled trials (RCTs) in PubMed, Scopus, and CENTRAL. Our main outcomes were mortality and adverse events. Secondary outcomes were bleeding control, rebleeding, blood transfusion, hospital stay. We evaluated the certainty of evidence using GRADE methodology. Results: We included 21 RCTs. The risk of mortality (RR: 1.01; 95%CI: 0.83-1.22), bleeding control (RR: 0.96; 95%CI: 0.91-1.02; I2=53%), early rebleeding (RR: 0.91; 95%CI: 0.66-1.24: I2=0%), late rebleeding (RR: 0.94; 95 CI: 0.56-1.60; I2=0%), blood transfusion (MD: 0.04; 95%CI:-0.31-0.39; I2=68%) and hospital stay (MD:-1.06; 95%CI:-2.80-0.69; I2=0%) were similar between T-V and O-S groups. Only 15 studies reported adverse events, which were significantly higher in the T-V compared to the O-S group (RR 2.39; 95%CI: 1.58-3.63; I2=57%). The certainty of evidence was moderate for the main outcomes, and low or very low for others. Conclusions: In cirrhotic patients with AVB, those treated with T-V had similar mortality risk compared to O-S. However, the use of T-V showed an increased risk of adverse events compared to O-S.